The night of the solstice - Smith, L. J. (Lisa J.) (New York : Aladdin, 2010)
Seven-year old Claudia, her older sister Alys, and twins Charles and Janie set out to rescue the sorceress Morgana, who is being held captive in a parallel world by the evil magician Cadal Forge, and stop Cadal from crossing over into their world and enslaving mankind.
5.4
5-8
5-8.
790
Keywords: Brothers and sisters -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Fiction; Magic -- Fiction; Fantasy; Siblings -- Fiction; Magic -- Fiction; Fantasy fiction; Fantasy fiction